ANALISIS PUTUSAN TINDAK PIDANA PENGGELAPAN DENGAN STUDI KASUS PUTUSAN NOMOR 1011/PID.B/2017/PN.JKT.SEL DAN PUTUSAN KASASI NOMOR 250.K/PID/2018 - amiliyanti, Ii amiliyanti; Warsifah , Warsifah (Journal Evidence Of Law, 2022)
This study aims to determine how the judge's consideration in deciding the criminal case and the legal relationship. In the results of this study, the South Jakarta District Court Judge concluded that the case was not a criminal act but a case of competition in civil society based on a cooperation agreement between the two parties and It is proven that one of the parties committed a breach of promise (default). This research uses a normative juridical approach, namely by reviewing or analyzing secondary data in the form of secondary legal materials by understanding the law as a set of regulations or positive norms in the statutory system regulate human life. From the research conducted, the authors obtained the following results: The judge at the South Jakarta District Court concluded that the case was not a criminal act but a civil competition case based on a cooperation agreement between the two parties and it was proven that one of the parties had committed a breach of contract (default). Based on the level 1 verdict, namely the action was proven but it was decided to be free which was handed down by the Judge, it needed to be reviewed so that a legal action could be submitted to the cassation level so that it could provide legal certainty in accordance with the law